Kisah Raja “Kafir” Nusirwan dalam Naskah Ki Sarahmadu Brajamakutha: Kajian terhadap Repertoire Penyusunnya - Binarung Mahatmajangga (Manuskripta, 2018)
Ki Sarahmadu Brajamakutha (KSB) is a manuscript collection of Widyapustaka, the library of Pakualaman Palace, Yogyakarta. This manuscript was written in Javanese script and language in macapat metre. KSB contains didactic stories on how to rule a kingdom, depicted in stories of prophets and kings mainly from the Middle East. Those stories are embeded in three texts: Tajusalatin, Hikayat Nawawi, and a text containing teachings of Paku Alam I and Paku Alam II. The “kafir king” story of Nusirwan appears in the manuscript as part of the Tajusalatin text. Despite being specifically mentioned as “kafir” or non-believer in the text, he is portrayed as a just king. The study of respon aesthetic of Wolfgang Iser is applied to the story of King Nusirwan as to how contemporary readers can understand the repertoire, making them easier to acquire the conventions on how the story was build, so that they can easily interpret the meaning as intended by the author. === Ki Surahmadu Brajamakutha (KSB) adalah manuskrip koleksi Widyapustaka, Perpustakaan Istana Pura Pakualaman, Yogyakarta. Manuskrip ini ditulis dengan aksara dan bahasa Jawa dalam tembang macapat. KSB berisi cerita didaktis tentang bagaimana aturan seorang raja, menggambarkan kisah nabi-nabi dan raja dari Timur Tengah. Cerita cerita tersebut terdapat di dalam tiga teks: Tajusalatin, Hikayat Nawawi, dan sebuah teks yang berisi ajaran-ajaran Paku Alam I dan Paku Alam II. Cerita “raja kafir” Nusirwan muncul di dalam sebuah manuskrip sebagai bagian teks Tajusalatin. Meskipun di dalam teks secara khusus disebutkan sebagai “kafir” atau tidak percaya, ia digambarkan sebagai raja yang adil. Studi tentang estetika respons Wolfgang Iser diterapkan pada kisah Raja Nusirwan tentang bagaimana pembaca kontemporer dapat memahami repertoar, membuat mereka lebih mudah untuk memperoleh konvensi tentang bagaimana cerita itu dibangun, sehingga mereka dapat dengan mudah menafsirkan makna sebagaimana dimaksud oleh penulis.